Natural Diversity of Frankia Strains in Actinorhizal Root Nodules from Promiscuous Hosts in the Family Myricaceae - Clawson, Michael L. (American Society for Microbiology, 1999)
Actinorhizal plants invade nitrogen-poor soils because of their ability to form root nodule symbioses with N(2)-fixing actinomycetes known as Frankia. Frankia strains are difficult to isolate, so the diversity of strains inhabiting nodules in nature is not known. To address this problem, we have used the variability in bacterial 16S rRNA gene sequences amplified from root nodules as a means to estimate molecular diversity. Nodules were collected from 96 sites primarily in northeastern North America; each site contained one of three species of the family Myricaceae. Plants in this family are considered to be promiscuous hosts because several species are effectively nodulated by most isolated strains of Frankia in the greenhouse. We found that strain evenness varies greatly between the plant species so that estimating total strain richness of Frankia within myricaceous nodules with the sample size used was problematical. Nevertheless, Myrica pensylvanica, the common bayberry, was found to have sufficient diversity to serve as a reservoir host for Frankia strains that infect plants from other actinorhizal families. Myrica gale, sweet gale, yielded a few dominant sequences, indicating either symbiont specialization or niche selection of particular ecotypes. Strains in Comptonia peregrina nodules had an intermediate level of diversity and were all from a single major group of Frankia.